Reading Musical Texts to Students on the Subject of Instrumental Performance and Ensemble - Z. Ziyavutdinova (Research Parks Publishing LLC, 2021)
This article is about good analysis of works in the study of piano and teaching the skills of reading from the sheet. It is important to gradually acquaint the reader with the basic principles of sheet analysis and reading methodology, and most importantly, to teach a meaningful approach to the text, not only to see all the notes, but also to listen to the musical content. To improve the ability to read notes, you need to get used to looking at the new text with your eyes. It is important to understand the size and ladotonality (to better store it in memory, we may suggest performing the appropriate gamma before analysis). Information is provided on understanding the structure of the work, where the melody is, the accompaniment, and how the sounds are distributed among the individual hands.